2018
DOI: 10.1002/job.2277
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic effects of personal initiative on engagement and exhaustion: The role of mood, autonomy, and support

Abstract: Researchers have neglected dynamic effects of proactive behavior on occupational well-being.We investigated effects of change in personal initiative over 6 months on changes in emotional engagement and exhaustion over the following 6 months. On the basis of the control-process theory on affect, we hypothesized that changes in positive and negative moods mediate these effects conditional upon employees' level of perceived organizational support. On the basis of action regulation theory, we assumed that change i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
81
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 118 publications
(242 reference statements)
3
81
0
Order By: Relevance
“…Given that withdrawal from work allows individuals to replenish their resource pool and to deal with negative emotions, it might also provide them with resources for further proactivity. In other words, we suggest that proactive work behaviours can be sustained over time (e.g., r = 66, over 1 year; Zacher et al ., ; r = .60, over 4 years; Frese, Garst, & Fay, ) in part because employees apply strategies, such as withdrawal, to actively manage their resources.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Given that withdrawal from work allows individuals to replenish their resource pool and to deal with negative emotions, it might also provide them with resources for further proactivity. In other words, we suggest that proactive work behaviours can be sustained over time (e.g., r = 66, over 1 year; Zacher et al ., ; r = .60, over 4 years; Frese, Garst, & Fay, ) in part because employees apply strategies, such as withdrawal, to actively manage their resources.…”
Section: Discussionmentioning
confidence: 99%
“…() found that personal initiative led to improved working conditions 4 years later. Other long‐term benefits of proactivity relate to reduction in workplace stressors, gains in supervisor support (Li, Fay, Frese, Harms, & Gao, ), increased autonomy, and emotional engagement (Zacher et al ., ). We encourage scholars to study the benefits and costs of proactivity simultaneously and over different periods of time to broaden our understanding of the temporal dynamics of the proactivity–well‐being relationship.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been argued that PWB can be associated with experiencing higher levels of stressors and strain, such as impaired well‐being (Bolino, Valcea, & Harvey, ; Cangiano & Parker, ). The results of few empirical studies on this potential ‘dark side’ of PWB support that PWB is related to elevated levels of strain and exhaustion (Fay & Hüttges, ; Pingel, Fay, & Urbach, ; Strauss, Parker, & O'Shea, ; Zacher, Schmitt, Jimmieson, & Rudolph, ).…”
Section: Introductionmentioning
confidence: 99%